2012
DOI: 10.4038/jccpsl.v16i2.4577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, trends and district differentials in teenage pregnancies

Abstract: Introduction Teenage pregnancies with their negative obstetric and foetal outcomes are a maternal and child health concern of the country. Objectives To study the prevalence, trends and district differentials in teenage pregnancies in Sri Lanka Methods Three main sources of available national level data were used in this study. They were : vital event registration data from the Registrar General's (RG) Department, data collected routinely by the Family Health Bureau (FHB), Ministry of Health through the Reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
2
1
Order By: Relevance
“…11 But NDHS (2011) reported that only 17% of teenage girls had already given birth or were pregnant with their first child. 12 Similarly the prevalence of teenage pregnancy in Sri Lanka (8%) 13 , in India (21%) 11 which were lower than our study.…”
Section: Discussioncontrasting
confidence: 49%
“…11 But NDHS (2011) reported that only 17% of teenage girls had already given birth or were pregnant with their first child. 12 Similarly the prevalence of teenage pregnancy in Sri Lanka (8%) 13 , in India (21%) 11 which were lower than our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Also, findings from a school-based questionnaire that formed part of the present project and are reported elsewhere, show findings that are comparable with recent national data [ 35 ] giving confidence that Badulla is not exceptional in any important respect. Nevertheless, recent analysis underscores the importance of acknowledging regional variations in levels and patterns of teenage pregnancy and the danger of extrapolation [ 2 ]. A further point worth mentioning is that our multivariate model was unable to explain a large amount of the variation in planned versus not planned pregnancies despite our inclusion of a wide range of variables, suggesting important unobserved factors.…”
Section: Discussionmentioning
confidence: 99%
“…In common with many parts of the world, teenage pregnancy is attracting increasing policy attention in Sri Lanka because of the risks it poses to maternal and infant health as well as to social and economic well-being [ 1 ]. Despite low levels compared to neighbouring countries and evidence of a decline in recent years, important differentials persist between regions, socioeconomic and ethnic groups [ 2 ]. Furthermore, there are concerns that pregnancy may have devastating consequences for teenage girls when it does occur, particularly if it happens outside of marriage [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%